2007
DOI: 10.1161/atvbaha.107.147421
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Promotes Ischemia-Induced Angiogenesis Through a PKG-Dependent Pathway

Abstract: Background— Peripheral artery disease (PAD) is a prevalent cardiovascular disorder that results in tissue ischemia which can progress to critical limb ischemia. Restoration of tissue perfusion in the setting of chronic ischemia through stimulation of arteriogenesis and angiogenesis remains a key therapeutic target for PAD. However, experimental therapeutics, including growth factor and gene therapy, have had little clinical success indicating the need for a better understanding of mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 38 publications
5
76
2
4
Order By: Relevance
“…We have recently reported that increasing intracellular cGMP through the inhibition of phosphodiesterase 5 significantly enhances ischemia induced angiogenesis through a phosphoglycerate kinase pathway (31). However, we found that nitrite therapy did not sustain a significant increase in ischemic tissue cGMP levels.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…We have recently reported that increasing intracellular cGMP through the inhibition of phosphodiesterase 5 significantly enhances ischemia induced angiogenesis through a phosphoglycerate kinase pathway (31). However, we found that nitrite therapy did not sustain a significant increase in ischemic tissue cGMP levels.…”
Section: Discussioncontrasting
confidence: 68%
“…Hind-limb ischemia was induced in wild-type mice, as we have reported by ligating the left common femoral artery proximal to origin of profunda femoris artery (31).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They include sildenafil (Viagra) and tadalafil (Cialis), which are prescribed to treat various medical conditions, including erectile dysfunction (ED), benign prostatic hyperplasia (BPH), and pulmonary arterial hypertension (PAH) [25]. The drugs' intended effect in patients is to produce vasodilation, but in animal studies both have been shown also to induce capillary formation in ischemic tissues/ organs [26][27][28][29][30][31]. These drugs regulate a key intermediate in metabolic pathways leading to capillary formation, as outlined elsewhere [32].…”
Section: Authorsmentioning
confidence: 99%